Pulse length dependence of photoelectron circular dichroism. Issue 44 (7th November 2022) - Lee, Han-gyeol; Ranecky, Simon T.; Vasudevan, Sudheendran; Ladda, Nicolas; Rosen, Tonio; Das, Sagnik; Ghosh, Jayanta; Braun, Hendrike; Reich, Daniel M.; Senftleben, Arne; Baumert, Thomas
Abstract : We investigated photoelectron circular dichroism (PECD) using pulses with various durations. From the experiment with fenchone, we found constancy of the PECD over a wide range of pulse durations and estimated lifetimes of internal conversions. Abstract : We investigate photoelectron circular dichroism (PECD) with coherent light sources whose pulse durations range from femtoseconds to nanoseconds. To that end, we employed an optical parametric amplifier, an ultraviolet optical pulse shaper, and a nanosecond dye laser, all centered around a wavelength of 380 nm. A multiphoton ionization experiment on the gas-phase chiral prototype fenchone found that PECD measured via the 3s intermediate resonance is about 15% and robust over five orders of magnitude of the pulse duration. PECD remains robust despite ongoing molecular dynamics such as rotation, vibration, and internal conversion. We used the Lindblad equation to model the molecular dynamics. Under the assumption of a cascading internal conversion, from the 3p to the 3s and further to the ground state, we estimated the lifetimes of the internal conversion processes in the 100 fs regime.